Pelatihan Pengembangan Desain Bangunan dan Manajemen Pengelolaan pada Peternakan Kambing di Kota Semarang - Mira Fitriana; Yusuf Wahyu Setiya Putra; Cisilia Sundari (Jurnal Kabar Masyarakat, 2025)
This community service aims to improve the quality of goat farming in Semarang City, especially at Ciliwung Farm. This activity focuses on two main aspects, namely building design development training and management training. Building design training emphasizes designing pens that meet goat health, comfort and productivity standards. Aspects such as ventilation, lighting, materials and cage layout are the main focus in this training. Meanwhile, management training is aimed at improving farmers' skills in managing the sales and marketing of goat products. Training materials cover marketing strategies, product development and financial management. It is hoped that through this activity, farmers at Ciliwung Farm can improve the quality of their products, expand their marketing network, and ultimately increase their income. The results of this community service show an increase in the knowledge and skills of breeders in designing good pens and managing goat farming businesses more effectively.